Better than chocolate - Roberts, Sheila, 1951- (Roberts, Sheila. 1951- Life in Icicle Falls., 2012)
Sweet Dreams Chocolate Company has been in the Sterling family for generations, ever since Great-Grandma Rose literally dreamed up her first fabulous recipe. But now it looks as if they're about to lose Sweet Dreams to the bank, and that would be a disaster, not only for the family but for the town of Icicle Falls, Washington. Can Samantha, the oldest daughter and new head of the company, come up with a way to save it? After Samantha does some brainstorming with her mother and sisters, inspiration strikes. They'll have a chocolate festival! Time is running out, but the Sterling women are determined and the town is behind them, so everything is bound to go smoothly. Or not. Events seem to be conspiring against Samantha, and her mother's attempts to help aren't helping. To make matters worse, the fate of her company is in the hands of her archenemy, Blake Preston, the bank manager with the football-hero good looks. It's enough to drive her to chocolate. But Blake's also enough to convince her that (believe it or not) there's something even better than chocolate.